Analisis Model Zmijewski (X-Score) dalam Memprediksi Financial Distress PT Krakatau Steel (Persero) Tbk dan PT Gunawan Dianjaya Steel Tbk - Dhia Rania Rajasa Putri; Hendra Sastrawinata; Agung Anggoro Seto (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2026)
This study aims to analyze the financial distress conditions experienced by PT Krakatau Steel (Persero) Tbk and PT Gunawan Dianjaya Steel Tbk in the period from 2015 to 2024 by utilizing the Zmijewski (X-Score) model. In addition, this study also aims to find out the level of accuracy of the model in predicting the company's financial condition. Financial distress refers to a condition of decline in financial performance, which can be an early sign of financial distress if not treated quickly. Therefore, a model is needed that can help detect possible financial difficulties for companies early on. In this study, a descriptive quantitative approach is used by utilizing secondary data consisting of annual financial statements of PT Krakatau Steel (Persero) Tbk and PT Gunawan Dianjaya Steel Tbk which can be accessed from the Indonesia Stock Exchange or the company's official website. This analysis was carried out using the Zmijewski model which refers to three financial ratios, namely Return on Assets, Debt Ratio, and Current Ratio. The results of this study show that PT Krakatau Steel (Persero) Tbk is in a healthy condition in 2015-2016, with an X-Score below 0, while in 2017-2024 it is predicted to experience financial distress because the X-Score value is above 0. Meanwhile, PT Gunawan Dianjaya Steel Tbk was consistently in good condition during the research period because all X-Score values were below 0. Thus, the Zmijewski model (X-Score) is more accurately applied to companies that have relatively stable financial conditions.